(untitled) (Ius Novum, 2021)
The article presents the issue of diffusion of innovation in the court networks in Poland with the use of the resources of knowledge of management. Attention is drawn to possible threats resulting from uncontrolled functioning of voluntary inter-organisational networks. The diagnosis was based on the source literature research method. It showed that first of all close cooperation within the created inter-organisational networks can produce the best economic results for both organisations and their individual participants. However, it does not concern networks working within the justice system because they do not aim to achieve economic results but only to improve the mechanism of information and knowledge exchange. Nevertheless, the need to improve the quality of adjudication cannot take place without the implementation of improvements facilitating it and the introduction of innovations in the field of management and diffusion of them in the court networks both horizontally and vertically.